2018
DOI: 10.3390/nu10101359
|View full text |Cite
|
Sign up to set email alerts
|

Association between Fasting Glucose Concentration, Lipid Profile and 25(OH)D Status in Children Aged 9–11

Abstract: Background: The aim of this study was to assess the relationship between vitamin D status and the prevalence of dyslipidemia and impaired fasting glucose (IFG) in children. Methods and Summary: 284 children (150 boys and 134 girls) aged 9–11 were included in the study. Children with deficient 25(OH)D (25-hydroxycholecalciferol) levels ≤20 ng/mL (50 nmol/L) were characterized by a more frequent occurrence of impaired fasting glucose (IFG) (Odd ratios (OR) = 1.966, 95% confidence interval (CI): 1.055–3.663; p = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…Previous studies have shown a close relationship between vitamin D levels and glycolipid metabolism. Most observational studies have shown that vitamin D was negatively correlated with FPG, 21,[28][29][30] TG, 24,[28][29][30][31][32][33] TC, 28,30,34,35 LDL-C 24,28,31 and positively correlated with serum HDL-C. 24,28,31,34 Szternel et al 29 showed that serum vitamin D level was negatively correlated with FPG and TC in children aged 9-11 years, and every 1 ng/mL reduction in 25(OH)D concentration was associated with a 0.013 mmol/L increase in FPG, a 0.25 mmol/L increase in TC, and a 0.015 mmol/L decrease in HDL-C.…”
Section: Relationship Between 25(oh)d Level and Glucose And Lipid Metmentioning
confidence: 99%
“…Previous studies have shown a close relationship between vitamin D levels and glycolipid metabolism. Most observational studies have shown that vitamin D was negatively correlated with FPG, 21,[28][29][30] TG, 24,[28][29][30][31][32][33] TC, 28,30,34,35 LDL-C 24,28,31 and positively correlated with serum HDL-C. 24,28,31,34 Szternel et al 29 showed that serum vitamin D level was negatively correlated with FPG and TC in children aged 9-11 years, and every 1 ng/mL reduction in 25(OH)D concentration was associated with a 0.013 mmol/L increase in FPG, a 0.25 mmol/L increase in TC, and a 0.015 mmol/L decrease in HDL-C.…”
Section: Relationship Between 25(oh)d Level and Glucose And Lipid Metmentioning
confidence: 99%
“…However, this relationship was not observed with regard to HDL cholesterol in healthy subjects. Szternel et al, (14) showed that serum vitamin D level was negatively correlated with fasting blood glucose and total cholesterol in children aged 9-11 years, and every 1 ng/mL reduction in 25(OH)D concentration was associated with a 0.013 mmol/L increase in fasting blood glucose, a 0.25 mmol/L increase in total cholesterol and a 0.015 mmol/L decrease in HDL-cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the observational studies have shown that vitamin D was negatively correlated with fasting blood glucose (12)(13)(14), total cholesterol, triglycerides, LDL-cholesterol and positively correlated with serum HDL-cholesterol (15)(16)(17)(18). In 2017, Ford et al, reported a negative relationship between 25(OH) D and triglycerides levels in hypotriglyceridemic patients (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the other study, neither IGF-1 nor 25(OH)D correlated with the circulating markers of bone turnover P1NP (N-terminal propeptide of type I procollagen) and CTX-1 (C-terminal telopeptide of type I collagen) examined in prepubertal and pubertal children with sufficient vitamin D status [16]. Even though the high occurrence of vitamin D concentrations below 20 ng/mL (50 nmo/L) in European pediatric populations evidence seems insufficient to recommend a screening for vitamin D deficiency [17,18]. It is plausible that the association between IGF-I and markers of bone metabolism vary in children with low levels of 25(OH)D. We aimed to investigate the association of serum bone turnover markers (P1NP and CTX) with low 25(OH)D levels (<20 ng/mL), compared to their interaction with IGF-1.…”
Section: Introductionmentioning
confidence: 99%